Correlation between velocity measurements from Doppler echocardiography and from M-mode contrast echocardiography. Issue 3 (March 1983) - Meltzer, R S; Diebold, B; Valk, N K; Blanchard, D; Guermonprez, J L; Lancée, C T; Peronneau, P; Roelandt, J
Abstract : The slope of an individual contrast trajectory on M-mode contrast echocardiography represents a physiological variable similar to that measured by Doppler echocardiography: the projection of the intracardiac velocity vector in the direction of the sound beam. To test the hypothesis that M-mode contrast echocardiography slope measurement can yield information quantitatively similar to Doppler measurements, we performed both simultaneously in 11 normal volunteers. A pulsed Doppler unit capable of simultaneous M-mode and Doppler display was used. Contrast was obtained by intravenous injection of 5% dextrose. Two independent observers measured velocity simultaneously by both techniques at eight to 16 points per subject. One observer repeated the measurements a month later. All subjects had contrast, and 10 had sufficient quality tracings for simultaneous Doppler and contrast slope measurements. The correlation between velocity measurements by both techniques was good, though velocities by Doppler echocardiography were less than by M-mode contrast echocardiography. We conclude that the component of flow velocity towards or away from the transducer can be measured from M-mode contrast trajectory slopes as well as by Doppler echocardiography. M-mode contrast echocardiography may provide a practical method for verifying or calibrating Doppler measurements in vivo.